Congenital Syphilis - J Gordon Millichap (Pediatric Neurology Briefs, 1990)
Seven infants with congenital syphilis who became symptomatic between 3 and 14 weeks of age are reported from the Bronx Municipal Hospital Center and Albert Einstein College of Medicine, Bronx, NY.